A simple model to estimate air temperature and soil temperatures under vertisol - DAS, H. P.; PUJARI , A. D.; CHOWDHURY, A. (MAUSAM, 1994)
Hnscd on a truncated s ine curve and exp onential fu nction models. diu rnal cha nges in air and soil temperat ures have I:....'en estima ted during day and night hours respect!....el..·. Each model uses o nlv fo ur parameters. viz.. maximum a nd mini mum temperature at va rious levels. the lime ()f sunset and durat ion t;f da yl night length. The models. when a pplied to experimental as well as independent dat a sets, were fo und to give reasonably accu rate estimates for a n>' lime of the day an d night except between I·B O1ST and sunset at the gro und surface.